Integrating Pedagogical Competence and Industrial Training to Improve Graduate Quality in Aviation Vocational Education - Ade Irfansyah; Yuyun Suprapto; Bambang Bagus Hariyanto (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
Vocational aviation education must deliver graduates whose competencies match strict regulatory and industry standards amid fast technological change. This study investigates how lecturer competence and industrial training jointly influence graduate quality in Indonesian state aviation polytechnics, and whether the learning process mediates these relationships. Using a quantitative ex-post facto design, we surveyed 274 final-year students from seven state aviation polytechnics selected through proportionate stratified random sampling. A structured questionnaire measured lecturer competence, industrial training, learning process, and perceived graduate quality. Data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0 to assess measurement validity and reliability, estimate direct and indirect effects, and evaluate model fit and predictive performance via path coefficients, R², Q², and the standardized root mean square residual (SRMR). The findings show that both lecturer competence and industrial training exert significant direct effects on graduate quality. The learning process is a strong predictor of graduate outcomes and partially mediates the effects of lecturer competence and industrial training, indicating that effective pedagogy and well-designed workplace learning reinforce each other. These results support integrating pedagogical development with industry-based learning strategies to strengthen graduate quality in aviation vocational education. Policymakers should align curricula, assessment, and partnership governance.